Implementasi Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) yang Mengintegrasikan Peer - Assessment untuk Meningkatkan Keterampilan Sosial Peserta Didik - Adawiyah, Siti Rabiatul (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to determine the role of the application of the Numbered Head Together (NHT) cooperative learning model that integrates peer-assessment to improve students' social skills. The peer-assessment instrument was developed using the Dick and Carey model. The trial of the peer-assessment instrument that has been developed was carried out at the MA Annajah Al-Halimy Education Foundation, West Lombok Regency. The peer-assessment instrument that has been developed is focused on assessing the social skills of students. The research data were analyzed descriptively. Assessment of students' social skills using peer-assessment is carried out at each meeting, namely for 4 meetings. The results showed that the social skills of students tended to increase at each meeting, namely: 4; 4.2; 4.3; and 4.4.